Investigation new sensing SnTiO3 as thin film light sensor - Mutukumaar Nallappan (Universiti Malaysia Perlis, 2008)
In this project, some research has been done on Tin dioxide (SnO2) and stannium titanate perovskite (SnTiO3) thin films. It has been known that tin dioxide has various applications, especially for gas sensor, light sensor, pressure sensor and humidity sensor. Main purpose of this project is to fabricate stannium titanate perovskite (SnTiO3) thin films using sol-gel method and compare it with tin (II) dioxide thin films.. In order to prepare tin dioxide (SnTiO3) thin film using sol gel method solution, the raw materials to be use which are Tin acetate, titanium dimethylformamide and 2-methoxyethanol need to be determined. All these materials will be added in correct ratio and with using spin coating to dope on the sample. After sample fabricated as correct process flow, the sample annealed with use rapid thermal analyzer (RTA). Three samples was annealing with three different times. The samples are RTA 5s, RTA 15s and RTA 30s. After that, sample has been successfully prepare and characterize of thin film produced using atomic force microscope (AFM) , scanning electron microscope (SEM) and potential method to find the surface roughness , grain size and I-V characteristics of stannium titanate perovskite thin film. I-V characteristics for longer annealing time (RTA 30s and RTA 15s) show the great increases of current value if we compare to RTA 5s (refer Table 4.6) . Apart from that, RTA 30s shows the great growth homogeneity of thin films if we compare to other two samples with result in decreasing of the Root Mean square (RMS) value and grain size. SnTiO3 also shows better sensing compare to SnO2 for all RTA 15 seconds and RTA 30 seconds.